2018
DOI: 10.1136/bmjopen-2017-020331
|View full text |Cite
|
Sign up to set email alerts
|

Are methodological quality and completeness of reporting associated with citation-based measures of publication impact? A secondary analysis of a systematic review of dementia biomarker studies

Abstract: ObjectiveTo determine whether methodological and reporting quality are associated with surrogate measures of publication impact in the field of dementia biomarker studies.MethodsWe assessed dementia biomarker studies included in a previous systematic review in terms of methodological and reporting quality using the Quality Assessment of Diagnostic Accuracy Studies (QUADAS) and Standards for Reporting of Diagnostic Accuracy (STARD), respectively. We extracted additional study and journal-related data from each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
1
13
0
1
Order By: Relevance
“…(Altmetrics is defined as the quantification of the digital footprint of a particular article that is not confined to the publishers and scientific community that is, social media, blogs and news outlets.) 10 This study is the first to examine the relationship between quality and impact in Otolaryngology. 12 Nieminen et al also did not find a significant relationship between the quality of psychiatric research among four journals and the total number of citations per article over 9 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Altmetrics is defined as the quantification of the digital footprint of a particular article that is not confined to the publishers and scientific community that is, social media, blogs and news outlets.) 10 This study is the first to examine the relationship between quality and impact in Otolaryngology. 12 Nieminen et al also did not find a significant relationship between the quality of psychiatric research among four journals and the total number of citations per article over 9 years.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it should include the impact of the article on clinical practice 9 . However, as with “quality” there is no consensus definition of “impact.” 10 In fact, impact can also be thought of as a multifactorial concept that changes depending on the point of view. For example, on a larger scale impact can be directly related to the appropriate dissemination of research thereby effecting policy making.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As already earlier critically discussed, they are not real measures for the quality of individual research (Pleger et al 2014). In this respect, a recent study addressed the question if methodological quality and completeness of reporting are associated with citation-based measures of publication impact (Mackinnon et al 2018). The authors performed a secondary analysis of a systematic review of dementia biomarker studies.…”
Section: Limitations Of Newqismentioning
confidence: 99%
“…While citation rates were weakly associated with completeness of reporting, none of these metrics was related to methodological rigor. They suggested that high publication usage and journal outlet is not a guarantee of quality and readers should critically appraise all papers regardless of presumed impact (Mackinnon et al 2018). Therefore, qualitative aspects are better addressed by advanced meta-analysis approaches using i.e.…”
Section: -2007mentioning
confidence: 99%